Perubahan Nama pada Akta Kelahiran dalam Hukum Perdata di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Badung - I Nyoman Aditya Nugraha; I Made Sarjana (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
The purpose of writing this paper is to examine what are the factors causing the name change on the birth certificate at the Badung Regency Population and Civil Registry Service and the legal consequences arising from the name change. This study uses empirical legal research methods, supported by a conceptual approach and laws and regulations. The data obtained is also the result of interviews with employees of the Badung Regency Population and Civil Registry Service. From the results of this study, it was found that the name change factor on someone's birth certificate was due to typing errors, the name was too long or short and the person concerned was sick. The legal consequences that are self-inflicted are related to the personal rights of the person concerned or their civil rights are affected and are a little difficult to realize.